Faktor -Faktor Yang Mempengaruhi Akuntabilitas Keuangan Desa pada Desa di Kecamatan Pahae Jae, Kabupaten Tapanuli Utara - Sahala Purba; Mulatua Silalah (JURNAL MUTIARA AKUNTANSI, 2021)
This study aims to analyze and determine the effect of SPI, HR Quality, Transparency and Supervision on Village Financial Accountability in the Village in Pahae Jae District, North Tapanuli Regency, either partially or simultaneously. This type of research is quantitative research and uses primary data. The data collection method used was a questionnaire given to village officials in Pahae Jae District, totaling 40 respondents. The data analysis method used in this research is descriptive analysis and multiple linear regression. The results of this study indicate that partially, SPI, Quality of Human Resources, and Supervision have a positive and significant effect while Transparency has a negative effect. Simultaneously SPI, Financial Accountability can be influenced by the quality of Human Resources, Transparency and Supervision in a positive and significant way in the Village in Pahae Jae District, North Tapanuli Regency.